Technology, Electoral Malpractice and the Crisis of Election Administration in Nigeria - Daniel Godwin (The Thinker)
The integration of technology into the various elements of the electoral value chain has contributed significantly to election administration both in established and transitional democracies of the world. In Nigeria, the integration of technology into the electoral process began in 2011 and has continued since then with significant positive impact on the outcome of all the elections held since 2011, especially the 2023 general elections. However, the outcome of the 2023 presidential election has been enmeshed in controversies and criticism from various stakeholders including local and international observers. One of the leading reasons for the controversy was attributed to technology (technical glitch) by INEC. This paper argues that the lack of transparency by INEC as revealed in its failure to electronically transfer results as promised and its refusal to upload results in real-time undermined the integrity of the 2023 presidential election. The paper examined the strategic contributions of the technological innovations used in the 2023 general elections. Principal-agent theory provided the framework, while a qualitative desk research design was adopted for the study. The paper relied on secondary sources of data. Findings showed that the introduction and integration of technologies into the electoral process cannot deal with the problem of electoral malpractice as a standalone initiative without the complementary uprightness from the EMBs. The paper concluded that the failure by INEC to keep to its guidelines as provided has to some extent compromised and eroded the confidence of Nigerians on the outcome of the 2023 presidential election.